Effects of ambient temperature and relative humidity on preterm birth during early pregnancy and before parturition in China from 2010 to 2018: a population-based large-sample cohort study - Wu, Yu; Yuan, Jie; Yuan, Yanling; Kong, Cai; Jing, Wenzhan; Liu, Jue; Ye, Hanfeng; Liu, Min (Frontiers in Public Health, 2023)
Background The progression of global warming and increase in instances of extreme weather have received considerable attention. We conducted a cohort study on women of childbearing age in Yunnan Province, examined the association between ambient temperature and humidity on preterm birth and evaluated the effects of extreme weather during early pregnancy and before parturition on preterm birth. Methods We conducted a population-based cohort study on women of childbearing age 18–49 years who participated in National Free Preconception Health Examination Project (NFPHEP) in Yunnan Province from January 1, 2010, to December 31, 2018. Meteorological data, namely daily average temperature (°C) and daily average relative humidity (%), were obtained from China National Meteorological Information Center. Four exposure windows were explored: 1 week of pregnancy, 4 weeks of pregnancy, 4 weeks before delivery, and 1 week before delivery. We used a Cox proportional hazards model and adjusted the potential risk factors for preterm birth to obtain the effects of exposure to temperature and humidity on preterm birth among the stages of pregnancy. Results At 1 week of pregnancy and at 4 weeks of pregnancy, the association between temperature and preterm birth was U-shaped. The correlation between relative humidity and the risk of preterm birth was n-type at 1 week of pregnancy. The correlation between preterm birth and temperature and relative humidity at 4 weeks before delivery and at 1 week before delivery is J-shaped. Low temperature and low humidity were protective factors against preterm birth, whereas high temperature and high humidity were risk factors for preterm birth. The effects of high temperature and extremely high temperature were the strongest at 4 weeks before delivery, with HRs of 1.417 (95% CI: 1.362–1.474) and 1.627 (95% CI: 1.537–1.722), respectively. The effects of extremely low humidity and low humidity were strongest at 1 week before delivery, with HRs of 0.681 (95% CI: 0.609–0.761) and 0.696 (95% CI: 0.627–0.771), respectively. Conclusion Temperature and relative humidity affect preterm birth differently for each pregnancy stage. The effects of meteorological factors on pregnancy outcomes such as premature birth should not be ignored.